2018
DOI: 10.5296/jas.v6i4.13945
|View full text |Cite
|
Sign up to set email alerts
|

Soil Microbial Community Response to Compost Addition to Nicosulfuron Contaminated Soil

Abstract: The toxicity of nicosulfuron to none target organisms is its downside, which has generated concerns about the herbicide in spite of its high herbicidal activity. Practices that would facilitate accelerated degradation of this herbicide will certainly be complementary to its use. A completely randomized design laboratory incubation experiment was carried out to examine the potentials of organic and mineral fertilizers to stimulate microbial activities in soil under the influence of the nicosulfuron herbicide. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This could have implications for the safety of sensitive rotational crops and the status of soil microbial indices. Research has shown that using herbicides for weed control may adversely affect the soil microbial status (Adejoro et al, 2018). Studies have also revealed that the sulfonylurea herbicides influence soil microbial activity and biomass in a variety of ways (Saeki and Toyota, 2004;Djuric and Jarak, 2006;Vischetti et al, 2000;Zabaloy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This could have implications for the safety of sensitive rotational crops and the status of soil microbial indices. Research has shown that using herbicides for weed control may adversely affect the soil microbial status (Adejoro et al, 2018). Studies have also revealed that the sulfonylurea herbicides influence soil microbial activity and biomass in a variety of ways (Saeki and Toyota, 2004;Djuric and Jarak, 2006;Vischetti et al, 2000;Zabaloy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%